THU0244 High prevalence of clinical spondyloarthritis features in patients with hidradenitis suppurativa. (12th June 2018) - Rondags, A.; van Straalen, K.R.; Arends, S.; van der Zee, H.H.; Prens, E.; Horvath, B.; Spoorenberg, A.
Abstract : Background: Hidradenitis suppurativa (HS) is a chronic debilitating inflammatory skin disease and is associated with several comorbidities. HS and spondyloarthritis (SpA) share several pathophysiological and clinical features, such as elevated cytokine levels of TNF-α and IL-17 and the association with inflammatory bowel disease. Recognition of clinical axial and peripheral SpA features might help to identify patients with a higher chance of having SpA. Objectives: To investigate the prevalence of self-reported clinical SpA features in HS patients and to identify HS patient characteristics associated with the presence of these features. Methods: In this cross-sectional study, a questionnaire concerning clinical SpA features was sent to all patients with a billing code of HS (between 2010 and 2016) in two tertiary HS referral centres in the Netherlands. First, questions were formulated based on the ASAS definitions for axial and peripheral SpA entry classification criteria: "back pain for ≥3 months with age of onset <45 years" and "peripheral arthritis, enthesitis or dactylitis" in past or present, respectively. Additionally, questions concerning other clinical SpA features (table 1) in past or present were asked. Questions were provided with proto-typical coloured pictures of SpA features for clarification. Prevalence of self-reported SpA features was calculated and comparative analysis was performed. Results: Overall, 47.2% (620/1313) of questionnaires were eligible for analyses. Included patients had a mean age of 43±14 years, 70% were female, mean BMI was 28.0±5.8, 84% were ex- or current smokers, and 25% had no HS symptoms at the time of the survey. In total, 67.1% (416/620) of HS patients fulfilled ≥1 of the four ASAS entry criteria. The entry criteria for axial and peripheral SpA were reported by 72.8% (303/416) and 27.2% (113/416), respectively. The large majority of patients (87%) reported ≥1 clinical SpA features in addition to the entry criteria: one feature by 137 (32.9%) patients, two by 121 (29.1%), three by 67 (16.1%), and ≥4 by 37 (8.9%). An overview and percentage of the clinical SpA features is presented in table 1. In comparison to patients without self-reported SpA entry criteria features (n=204), patients fulfilling the ASAS entry criteria were more frequently female (p<0.001), had higher BMI (p<0.001), more often positive smoking history (p=0.001), longer HS disease duration (p=0.012), and showed more active HS symptoms at time of the survey (p<0.001). Conclusions: Clinical axial and peripheral SpA features are common in HS patients, especially in the 'classic' HS patient (female, overweight, smoker), with longer HS disease duration and symptoms of active HS. Disclosure of Interest: A. Rondags: None declared, K. van Straalen: None declared, S. Arends: None declared, H. van der Zee Consultant for: Abbvie, InflaRX, E. Prens Grant/research support from: AbbVie, AstraZeneca, Janssen, Pfizer, Consultant for: AbbVie, Amgen, Celgene, Janssen, Galderma, Novartis, Pfizer, B. Horvath Grant/research support from: Abbvie, Janssen-Cilag, Novartis, Consultant for: Abbvie, Janssen-Cilag, Novartis, A. Spoorenberg Grant/research support from: Pfizer, Abbvie, Consultant for: Pfizer, Abbvie, MSD, UCB, Novartis